(untitled) (Research, Society and Development, 2021)
Since the beginning of the COVID-19 pandemic, the mortality profile and associated risk factors have been widely traced in different parts of the world. So, we analyse the occurrence of deaths by bulletin of the State Health Department of Sergipe, Brazil published on June 9, 2021. Data were analyzed descriptively and inferential using R software. Sergipe registered 5,295 deaths due to the new coronavirus during the first 15 months of the pandemic, 2,592 (49.0%) in 2020 against 2,703 (51.1%) in 2021. The victims presented mean age of 65.3 (±17.4) years old, with predominance of male (56.2%), from the metropolitan region of Aracaju (56.0%) and who have some comorbidity (71.3%). It was observed a significant difference in the median age in relation to the year of death, sex and comorbidity, in addition year of death with age and location, with increase in the proportion of deaths among people aged 30 to 59 years from 25.6% in 2020 to 33.8% in 2021. In people aged 60 years or more, however, there was a decrease in 2020, this age group represented 71.1% of deaths and rose to 63.6%. These variations of mortality profile can be attributed to the return of work activities involving the adult age group, as well as the vaccination of the elderly, as priority group. Thus, we observed that sex, age and the presence of comorbidities were the factors with the greatest influence on mortality from COVID-19.